THE INFLUENCE OF BUY 1 GET 1 PROMOTION ON THE SALES OF PRODUCTS IN CONSUMER ATTRACTION POWER - ahmad abdul majid (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
This study aims to determine whether sales promotions, the attractiveness of buy 1 get 1 can affect the product purchase . The appeal of consumers un tuk buy a product with the promotion of relatively high . Promotion is a communication activity carried out by a person or company with the community with the aim of allowing something (goods, services, brands, companies) to the community and at the same time influencing the wider community to buy and use the product. This type of research is carried out by the method of explanatory research or explanatory research with a quantitative approach. Variables used in this study include; cashback promotions, promotions, consumer purchasing power decisions. The population of this study is the wider community in DKI Jakarta, which was carried out randomly with a sample of 99 respondents taken using purposive sampling techniques and data collection methods using questionnaires. Analysis of the data used is descriptive analysis and path analysis.